Narasi Pekerja Perempuan di Media Televisi Lokal - Machmud, Melati Puspitasari; Astagini, Nuria; Rachmat, Ikbal; Yuliastiani, Indriati (JOURNAL OF SCIENTIFIC COMMUNICATION (JSC), 2023)
Working in television media are still associated with men. Therefore, the presence of women workers in television media is often considered insignificant. The number of women working in the media industry is still very limited. Therefore, many media company do not have sufficient policies which accommodate the voices of women workers. This is felt by women workers in the local television media who have to struggle to maintain their position amidst the domination of their co-workers, who are mostly male. Narratives from women workers who work in local media companies can provide a reality of the industrial world which limits the space for workers just because they are women. Therefore the purpose of this research is to analyze and describe the narratives which are the standpoints of women workers working in local media companies. This study uses Standpoint theory which assumes that women have different perceptions, opinions, and perspectives on the world than men. The paradigm used in this study is the critical constructivism paradigm. Using a purposive sampling technique, three research subjects were obtained. Through in-depth interviews and observations, it was discovered that women workers accept their position as a minority in the scope of work as a consequence of the jobs they choose. However, they struggle to have space to speak out and defend their self-respect, instead of being the object of harassment and discriminatory actions by male workers. The standpoint of women workers shows that they are aware of their very vulnerable position. Therefore, they have various strategies to fight for and maintain their position as media workers, which is equal to their male counterparts. Keywords:  women, workers, television media, standpoint, gender